A highly selective fluorescent chemosensor for NADH based on calix[4]arene dimer. Issue 5 (2nd February 2017) - Zadmard, Reza; Akbari-Moghaddam, Peyman; Darvishi, Shukufe; Mirza-Aghayan, Maryam
Abstract: A new calix[4]arene dimer (C4D ) has been designed and synthesized as a fluorescent chemosensor for the recognition of NADH in aqueous media. This chemosensor showed unique selectivity toward NADH over various biomolecules, with a detection limit of 24.5 nM (16.3 μg L −1 ). Moreover, the stoichiometry of theC4D -NADH complex formed was found to be 1:1 and the binding constant was calculated to be 3.74 × 10 5  M −1 . Graphical abstract: